Local Wisdom of Capital in Development in Aceh Besar Regency - Helmi Satria; Efi Safira (Budapest International Research and Critics University, 2021)
Development using a centralized approach without developing community self-reliance today is unable to solve various social problems due to the lack of developing community presence in development activities. Community development will be effective when local wisdom is used as capital by utilizing existing organizations or habits at the local level. In this case, the government as the party that provides encouragement and assistance in implementing development is enough to act as a facilitator and motivator. Let the community formulate and implement the types of development activities and how to implement them. Based on this description, the objectives of this research are as follows: (1) To describe local wisdom as development capital in the study of social reality in Aceh Besar Regency. (2) To analyze the forms of local wisdom used in development in Aceh Besar Regency. This study uses a qualitative approach in describing local wisdom as development capital with data collection techniques that the researchers did through observation, in-depth interviews and documentation. The research informants were determined by purposive sampling with consideration of their experiences in social life and their personalities. The results of the study indicate that the high level of local wisdom possessed by the people of Aceh Besar Regency is caused by a strong social base, as well as the historical orientation and dimension of the formation of social values ​​and norms in social life due to the similarity of religion and kinship relations, so that it has an impact on implementation. development. Local wisdom that supports development in the form of agreements, cooperation, participation that is used as a habit can produce high cohesiveness in the people of Aceh Besar, and there is a passion for charity in carrying out development as well as a sense of volunteerism that evokes self-reliance as well as a strong sense of social solidarity in society. Local wisdom possessed by members of the Aceh Besar Regency community is used as capital in development in the form of trust, social networks and social norms that are still strong enough to support the realization of development in accordance with community expectations.